Global expansion of Vibrio parahaemolyticus threatens the seafood industry: Perspective on controlling its biofilm formation. (15th March 2022) - Wang, Dan; Flint, Steve H.; Palmer, Jon S.; Gagic, Dragana; Fletcher, Graham C.; On, Stephen L.W.
Abstract: As global warming increases the geographical range and frequency of Vibrio parahaemolyticus infections, its formation of biofilms providing bacteria greater resistance to stress and contributing to the persistence of pathogens, is threatening the seafood industry. V. parahaemolyticus has a number of advantages leading to biofilm formation. This study reviews recent advances in understanding V. parahaemolyticus biofilm formation on biotic and abiotic surfaces, discusses research gaps in the mechanism of biofilm formation and examines promising biofilm control strategies to overcome current limitations of chemical disinfectant. This information will deepen our understanding of V. parahaemolyticus biofilm formation, as well as help design and optimize V. parahaemolyticus biofilm control strategies for the seafood industry. Highlights: The global expansion of Vibrio parahaemolyticus is threatening seafood safety and human health. The persistence of V. parahaemolyticus biofilm may induce recurrence of pathogens and complicate hygienic treatment. Biofilm formation in V. parahaemolyticus is controlled by an integrated network of transcriptional regulators. Novel strategies provide promising alternatives to chemical disinfectant treatments that are ineffective against biofilms.